SHARE
SPREAD
HELP

The Tradition of Sharing

Help your friends and juniors by posting answers to the questions that you know. Also post questions that are not available.


To start with, Sr2Jr’s first step is to reduce the expenses related to education. To achieve this goal Sr2Jr organized the textbook’s question and answers. Sr2Jr is community based and need your support to fill the question and answers. The question and answers posted will be available free of cost to all.

 

#
Authors:
Linda Null ,julia Lobur
Chapter:
Boolean Algebra And Digital Logic
Exercise:
Exercises
Question:6 | ISBN:9780763704445 | Edition: 3

Question

6. Use the Boolean identities to prove the following:

a) The absorption laws

b) DeMorgan’s laws



TextbookTextbookTextbookTextbookTextbookTextbookTextbookTextbookTextbookTextbookTextbookTextbookTextbookTextbookTextbookTextbookTextbook

Answer

a)The absorption Law:

Give algebraic proof of absorption law of boolean algebra.

(i)

X+XY=X
It can be proved algebraically as

L.H.S. = X+XY
           = X(1 + Y)

Putting 1+ Y = 1   (ref. properties of 0, 1 Theorem 1)
X.1=X = R.H.S. (ref. properties of 0, 1)


Hence proved.

(ii)

X(X + Y) = X

The algebraic proof of this law.

L.H.S. = X(X+Y)= X.X + XY
= X.X + XY
= X + XY  (X.X=X: Indempotence Law)
= X(1 + Y)
= X.1  (using 1+ Y =1, properties of 0, 1)
= X (X.1=X, using property of 0, 1)
= R.H.S


Hence proved.

b)DeMorgan's Law:

 

Statements :
1. (x+y)'=x'.y'
2..(x.y)'=x'+y'

Proof:
Here we can see that we need to prove that the two propositions are complement to each other.
We know that A+A'=1 and A.A'=0 which are annihilation laws. Thus if we prove these conditions for the above statements of the laws then we shall prove that they are complement of each other.

For statement 1:
We need to prove that:

(x+y)+x'.y'=1  and  (x'.y').(x+y)=0

Case 1.

 

(x+y)+x'.y'=1

 

LHS

(x+y)+x'.y'=(x+y).(x+x')+x'.y'

= x.x+x.y+y.x'+x'.y' = x+x.y+y.x'+x'.y'   {Using Distributive Property)

= x+x.y+x'(y+y')

=x+x.y+x'=x+x'+x.y

=1+x.y=1=RHS


Hence proved.

 

Case 2.

 

(x'.y').(x+y)=0

 

LHS:

(x'.y').(x+y)=x.(x'y')+y.(x'.y')

=x.0+o.x'=RHS

Hence proved.

 

For statement 2:


We need to prove that:

 

x.y(x'+y')=1  and  x.y.(x'+y')=0

 

Case 1.

x.y+(x'+y')=1
LHS:

x.y+(x'+y+)=(x+x'+y').(y+x'+y')            {We know that A+BC=(A+B).(A+C)}

=(1+y').(1+x')=1=RHS
 

Hence proved.

 

Case 2.

x.y.(x'+y')=x.x'.y+x.y.y'

=0=RHS

Hence Proved.

This proves the De-Morgan’s theorems using identities of Boolean Algebra.

0 0

Discussions

Post the discussion to improve the above solution.